2014
DOI: 10.1107/s1600576714020445
|View full text |Cite
|
Sign up to set email alerts
|

Structure and composition of bismuth telluride topological insulators grown by molecular beam epitaxy

Abstract: The structure and composition of Bi2Te3−δ topological insulator layers grown by molecular beam epitaxy is studied as a function of beam flux composition. It is demonstrated that, depending on the Te/Bi2Te3 flux ratio, different layer compositions are obtained corresponding to a Te deficit δ varying between 0 and 1. On the basis of X‐ray diffraction analysis and a theoretical description using a random stacking model, it is shown that for δ≥ 0 the structure of the epilayers is described well by a random stackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 41 publications
11
75
0
Order By: Relevance
“…Fulop et al [81] found that a beam equivalent pressure ratio below 17 favored the growth of Bi 4 Te 3 , though this growth was not conducted using a cracking source. When Steiner et al [85] studied Bi 2 Te 3-δ (where δ is the Te deficit) they found that δ close to 0 produced the most uniform quintuple layer steps despite good streaky reflection high energy electron diffraction (RHEED) being present for δ from 1 to 0, as shown in Figure 8. Therefore, RHEED may not be a reliable metric for achieving the correct composition.…”
Section: Bi 2 Tementioning
confidence: 99%
“…Fulop et al [81] found that a beam equivalent pressure ratio below 17 favored the growth of Bi 4 Te 3 , though this growth was not conducted using a cracking source. When Steiner et al [85] studied Bi 2 Te 3-δ (where δ is the Te deficit) they found that δ close to 0 produced the most uniform quintuple layer steps despite good streaky reflection high energy electron diffraction (RHEED) being present for δ from 1 to 0, as shown in Figure 8. Therefore, RHEED may not be a reliable metric for achieving the correct composition.…”
Section: Bi 2 Tementioning
confidence: 99%
“…Indeed, recent compositional analysis of bulk crystals has revealed that Mn may also be incorporated interstitially as in Mn x Bi 2 Te 3 [14], but no precise information on the actual incorporation sites was reported. It has also been suggested that Mn may incorporate in excess Bi-Bi double layers [12,15] easily formed in bismuth telluride when grown under tellurium deficient conditions [12,18,19]. Thus, the mechanism of Mn incorporation has been rather unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The growth temperature was set constant to 350 °C for all samples, the layer thicknesses were between 350 and 500 nm. The details of the growth can be found in [15].…”
Section: Methodsmentioning
confidence: 99%
“…In the intermediate cases, only some diffraction maxima survive. In order to describe this effect we developed a statistical model of a Bi m X n lattice assuming that the number of QLs between two following Bi-Bi DLs is random with the mean value N. In reference [15] we presented the details of the model and a formula for the diffracted intensity averaged over all random sequences of QLs and DLs. The mean result of the model connects the full-widths at half maxima (FWHMs) δQ of the modulation satellites with the root-mean square (rms) deviation σ N of the number of QLs between two DLs according to …”
Section: Analysis Of the Diffraction Datamentioning
confidence: 99%
See 1 more Smart Citation